COVID-19 RT-PCR testing for elite athletes - Rankin, A.; Massey, A.; Falvey, E. C.; Ellenbecker, T.; Harcourt, P.; Murray, A.; Kinane, D.; Niesters, B.; Jones, N.; Martin, R.; Roshon,M.; McLarnon, M. E. D.; et al. (British Journal of Sports Medicine, 2021)
This infographic outlines evidence-based recommendations on COVID-19 reverse transcriptase PCR (RT-PCR) testing in elite sport settings, aiming to protect personal and population health, and acknowledging resources and expertise that are often available in elite sport. Public health recommendations vary by country and region, and protocol decisions should be made in consultation with relevant public health authorities.